2011
DOI: 10.1016/j.jjie.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of liquidity shock to bank credit: Evidence from the deposit insurance reform in Japan

Abstract: Finding the causal effects of liquidity shocks on credit supply is complicated by the endogenous relation between loan demand and liquidity position of banks. This paper attempts to overcome this problem by exploiting, as a natural experiment, the exogenous deposit outflow prompted by the removal of a blanket deposit guarantee on time deposits in Japan. We find that just as the government placed a cap on insurance for time deposits in 2002, weak banks suffered from a large outflow of partially insured time dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In aggregate-level modeling, however, deposits are usually avoided due to the possibility of spurious correlation that does not adequately reflect structural relationships (Hülsewig et al, 2004). At the same time, when the deposits trend may be considered with certainty as exogenous, this indicator is appropriate for the purpose of loan supply modeling (for examples, see Khwaja and Mian, 2008;Paravisini, 2008;and Imai and Takarabe, 2009). Given that the CBR's forex purchases and fiscal policy measures have direct effect on money stock in Russia, we see the supposition of exogeneity as plausible.…”
Section: Model Specification and Data Issuesmentioning
confidence: 99%
“…In aggregate-level modeling, however, deposits are usually avoided due to the possibility of spurious correlation that does not adequately reflect structural relationships (Hülsewig et al, 2004). At the same time, when the deposits trend may be considered with certainty as exogenous, this indicator is appropriate for the purpose of loan supply modeling (for examples, see Khwaja and Mian, 2008;Paravisini, 2008;and Imai and Takarabe, 2009). Given that the CBR's forex purchases and fiscal policy measures have direct effect on money stock in Russia, we see the supposition of exogeneity as plausible.…”
Section: Model Specification and Data Issuesmentioning
confidence: 99%
“…Scientific research (Andries & Billon, 2010;Angkinand & Wihlborg, 2010;Bijlsma & Van Der Wiel, 2015;Forssbaeck, 2011;Gómez-Fernández-Aguado, Partal-Ureña, & Trujillo-Ponce, 2014;Imai & Takarabe, 2011;Lin, 2015;Prean & Stix, 2011) emphasised that the deposit insurance system not only contributes to the protection of depositors, but also affects their own bank decisions and the entire banking system, which is especially important in the case of the common European Union financial system. The common risk-based E.U.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that banks decrease their regulatory capital ratios when they encountered higher illiquidity as defined in the Basel III accords or when they created more liquidity. Imai and Takarabe (2011) investigated the causal impacts of liquidity shocks on credit supply by the endogenous relationship between loan demand and liquidity position of banks. They reported that during the period of transition from a blanket guarantee to a partial guarantee, weak banks influenced from a large outflow of partially insured time deposits.…”
Section: Introductionmentioning
confidence: 99%